(untitled) (Al-Academy, 2023)
The concept of aesthetics is one of the postmodern propositions, and it is one of the branches of philosophy that examines beauty, its standards and theories, and it is a holistic concept that includes several concepts, including the beautiful, the ugly, and the sublime.The concept of aesthetics dealt with several studies in general (and in the field of architecture in particular), and the problem of aesthetics is in the blurring of the relationship between aesthetics and architectural criticism, based on the research hypothesis which states that there is a relationship between aesthetics and architectural criticism. The importance of the research in accommodating aesthetic standards and bases of evaluation that increases the possibility of enjoying the aesthetic taste of architecture, which highlights the relationship between aesthetics and architectural criticism. As for the research method, it was represented by studying the concept of aesthetics through two main axes, The first axis: establishing a theoretical information base to define the concept of aesthetics through the investigation and analysis of propositions and literature in the various fields of knowledge that directly or implicitly dealt with the concept of aesthetics and the architectural dimension, The second axis: investing this information base and enhancing it with architectural proposals and studies and extracting the close relationship between aesthetics and architectural criticism.The research found that there is a close relationship between aesthetics and architectural criticism, through the aesthetic judgment of the products of architecture through aesthetic criticism of the aesthetic experience according to aesthetic critical foundations (subjective or objective or both) as a broader perspective the aesthetic phenomenon